2022
DOI: 10.1097/aci.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of allergen profile, sensitization patterns and Allergic Rhinitis in SouthEast Asia

Abstract: Purpose of reviewTo highlight the characteristics of allergic rhinitis, local allergic rhinitis (LAR), and importance of allergens in Southeast Asian countries. Recent findingsThe Asia-Pacific region is very diverse with disparities in the epidemiological data between countries as well as in the unmet needs. The prevalence of allergic rhinitis has markedly increased in the past decades, with a high variation between countries, ranging from 4.5-80.3%. In terms of LAR, the reported prevalence in Southeast Asia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Allergic rhinitis (AR) is an allergic reaction in the nasal mucosa to inhaled allergens, which is associated with several physiological procedures such as the production of allergen‐specific immunoglobulin E (IgE), activation of T‐helper (Th) cells, and chronic inflammation 1,2 . Globally, AR is a prevalent disease with steadily increasing incidence in low‐ and middle‐income countries, partly due to the increasing level of pollutants such as traffic waste and particulate matter 2.5 (PM2.5) 3–5 . The current medical management for AR mainly includes antihistamines, intranasal corticosteroids, and allergen‐specific immunotherapy; however, these treatments merely relieve the symptoms of AR 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis (AR) is an allergic reaction in the nasal mucosa to inhaled allergens, which is associated with several physiological procedures such as the production of allergen‐specific immunoglobulin E (IgE), activation of T‐helper (Th) cells, and chronic inflammation 1,2 . Globally, AR is a prevalent disease with steadily increasing incidence in low‐ and middle‐income countries, partly due to the increasing level of pollutants such as traffic waste and particulate matter 2.5 (PM2.5) 3–5 . The current medical management for AR mainly includes antihistamines, intranasal corticosteroids, and allergen‐specific immunotherapy; however, these treatments merely relieve the symptoms of AR 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…3 In the Asia-Pacific region, the prevalence of AR is ranging between 4.5-80.3%. 5 Meanwhile, the prevalence of AR in Indonesia is not known for certain because there is no national data on this matter, but there was a study on a class of 2010 medical students of Padjadjaran University which showed that the prevalence of AR was 38.2%. 6 Allergic rhinitis can decrease quality of life by impairing cognitive function and sleep and also causing fatigue and irritability.…”
Section: Introductionmentioning
confidence: 99%